Asbestos exposure assessment for ceiling tile removal using glove bags in small indoor facilities - Sung Ho Hwang; Moonjong Yun; Doo-Young Kim; Byung Kyu Lee; Dae Sung Lim (Scientific Reports)
Abstract This study aimed to evaluate the safety of small-scale asbestos dismantling and removal work, especially ceiling tile removal using glove bags (GBs), and to investigate the potential for asbestos dispersion in GBs during ceiling material removal to propose safe work practices and related regulations. Asbestos exposure assessment was conducted at five asbestos-containing ceiling tile dismantling sites nationwide. Air sampling was performed during ceiling tile removal at four points per site: near workers’ respiratory tract, at the GB fixed boundary, inside the GB, and within the general work area. Phase contrast microscopy was applied to determine asbestos. The results indicated that airborne asbestos concentrations varied by region, with the highest levels detected inside the GB. Elevated concentrations were also observed near workers’ respiratory tract. During ceiling tile removal, asbestos concentrations increased as the number of ceiling tiles removed rose from one to three. Proper sealing of asbestos dust to prevent leakage from the GB is essential, and removing ceiling tiles individually rather than in batches effectively reduces asbestos concentrations.